The Use of Role Play Method to Improve Speaking Skills - Adib Ahmada; Lailatul Munawaroh (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Language is often considered one of the most difficult aaspects of language learning. For most foreign language learners, English has become the most important language in this world a fact that cannot be denied. all the human in the world that use language. Students need to be able to compered and produce spoken and writing. And also, meaning in a key word was speaking is the process of building and sharing meaning through the use of verbal and non-verbal symbols in a variety of contexts. Role play is a method of acting out particular ways of behaving or pretending to be other people who deal with new situations.This research goal is to describe the process of how the use of role play method to improve speaking skills in the communicative class of ASYEE (as-syafi'iyyah english excellent) course Darussalam boarding school in the academic year 2021/2022. The researcher limited the scope of the research only on the student’s speaking skillss. Especially the imitative speaking. The researcher only focuses on seven students. There were those whose average scores were 60,00 less than the KKM standard determined at the institution. This research method used the classroom action method (CAR), And in this research contains one cycle which every single cycle contains two meetings. Moreover, this research carried out according to classroom action research process. Steps such as: a preliminary study, planning, implementing, observing, and reflecting. This classroom action research involved 23 students. but There are seven students in the research, because of their scores less than the KKM standard that has been determined at the institution. Based on analysed data, the score in the preliminary study was 28% student’s getting a minimum score of KKM. And then, it was decreased in the cycle 1 that 8%. And in cycle 2 was 0% students minimum of KKM. Therefore, the role play technique can significantly improve students' problems in speaking skills. Speaking skill can increase when they try to focus and relax on the material that the teacher has conveyed. If students have focused on the material, then understanding the material will be easier and students are not easily bored with the teacher's explanation. Based on Student Speaking Score from teacher in cycle 1, after using Role Play Method. The students speaking score of ASYEE (Assyafiiyyah English Excellent) in academic 2021/2022 after using the role play method being increased 80%.